Optimization and performance evaluation of silk fabrics dried in the domestic dryer. Issue 6 (3rd June 2018) - Wei, Yuhui; Gong, R. Hugh; Su, Zhaowei; Wang, Xu; Ding, Xuemei
Abstract: To determine the optimal drying procedure for large load and non-ironing procedure for small load when silk fabrics were drying-cared in daily usage; change in appearance, mechanical properties and microstructure of silk fabrics before and after drying with various drying parameters (heater power, air velocity and drum-rotating speed) were investigated. Results revealed that the performance of silk fabric after drying is more sensitive to air velocity (humidity of drying-air) rather than heater power (temperature). Heater power of 3000W, air velocity of 8.5m/s and drum rotating speed of 45-50rpm (No.2) was proved to be optimal for drying silk fabrics due to its ideal smoothness appearance, dimensional stability and drying efficiency. When consumers dry a small amount of clothes, a drying procedure of heater power of 3000W, air velocity of 8.5m/s and drum-rotating speed of 0rpm (No.6) is more reasonable procedure because it reduces or eliminates ironing. And indicating drying in dryer can be an effective alternative to indoor-drying or sunlight-drying if suitable procedure being set. This finding provided reference for manufacturers to design and improve of dryers, especially for drying procedures optimization of delicate textiles, and consumers a feasible care method without reducing the quality of fabric.